Pengaruh Konsentrasi Pupuk Organik Cair Kulit Pisang Kepok terhadap Pertumbuhan dan Hasil Tanaman Bayam Merah (Amaranthus tricolor L.) - Natania, Inggrid Olivia; Pradnyawathi, Ni Luh Made; Astawa, I Nyoman Gede (Agrotrop : Journal on Agriculture Science; Vol 14 No 1 (2024), 2024)
Effect of Concentration of Kepok Banana Peel Liquid Organic Fertilizer on Growth and Yield of Red Spinach ( Amaranthus tricolor L.) . This study aims to determine the effect and the best concentration of kepok banana peel liquid organic fertilizer which gave the highest growth and yield for red spinach ( Amaranthus tricolor L.). This study used a completely randomized design (CRD) with 6 treatments, namely 0, 10, 20, 30, 40 and 50 ml/l with 4 repetitions. The research was conducted in the greenhouse of the Experimental Garden of the Faculty of Agriculture and Agronomy and Horticulture Laboratory, Udayana University from November 2022-February 2023. The application of fertilizer had an effect and a concentration of 50 ml/l was the best concentration which gave the highest yield which increased plant height 29 dap 139% (19.48 cm), number of leaves 29 dap 358.06% (35.50 strands), leaf area 875.30% ( 39.50 cm 2 ), root length 154.39% (26.33 cm), fresh weight of plant tops 407.83% (26.56 g), oven dry weight of tops of plants 493.54% (3, 68 g), root fresh weight 389.7% (12.83 g), root oven dry weight 103.22% (1.26 g), root shoot ratio 168.31% (2.71) and leaf chlorophyll content 220 .85% (25.38 units) compared to control (8.15 cm, 7.75 strands, 4.05 cm 2 , 10.35 cm, 5.23 g, 0.62 g, 2, 62 g, 0.62 g, 1.01 and 7.91 units).